Logistics resources as a source of competitive advantage for logistics service providers - Zuraimi Abdul Aziz; Razli Che Razak; Mohd Rafi Yaacob; Rosliza Che Rahim (2015)
A competitive advantage is an element of long-term success, seen as a determinant of survival and development in a long term. Highly competitive markets aimed at reducing cost and continuously satisfying customers, therefore, the effectiveness and efficiency of Logistics Service Providers in delivering their service is fundamental to sustain and compete in the market. Competitive advantage is a kind of distinction, that ensures LSPs better results, and which can be realized by means of carefully chosen strategy of competition. In addition, both globalization and liberalization have led to many competitors entering the market which resulted to global LSPs increased and created a great pressure on logistics systems, which makes inevitable changes for local LSPs. The LSPs must increase values to their customers by providing logistics service more efficiently than their competitors. This study attempts to investigate the logistics resources as a source for competitive advantage in this industry. The semi-structured interviews with top managers were conducted at five Logistics Service Provider firms. The finding indicated that LSPs have acquiring physical, management expertise, technology, relational and organizational resources in their firms. However, management expertise and relational resources are more significant impact towards to the competitive advantage for LSPs.